Quality of Life and Metabolic Indicators of Patients with Type 2 Diabetes: A Cross-Sectional Study in Iran - Mohammad Hossein Kaveh; Keramat Noori; Mahin Nazari; Khadijeh Khademi (International Journal of Endocrinology)
Background. The World Health Organization (WHO) has considered type 2 diabetes mellitus (T2DM) a major global health challenge because of its high prevalence worldwide. T2DM can affect patients’ personal, social, and economic statuses. On the other hand, due to the increasing prevalence of T2DM, Quality of Life (QOL) has received more attention in recent years. Objective. The present study was conducted to investigate the relationships between QOL and physical activity level, body mass index, fasting blood sugar, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglyceride, total cholesterol, HbA1c, and systolic and diastolic blood pressure among Iranian patients with uncomplicated T2DM. Methods. This cross-sectional study was conducted on 135 participants selected through consecutive sampling. The study data were collected using International Physical Activity Questionnaire and Short-Form Health Survey Questionnaire. Then, the data were entered into the SPSS ver. 28 software, and Pearson’s correlation was used to measure the correlation between the variables. Linear regression was also employed. The significance level was set at 0.05. Results. The significant association was observed between gender (p=0.007), HDL level (p=0.02), and gender-adjusted physical activity (p=0.002) with QOL. Conclusions. Due to the association between physical activity and HDL level with QOL in patients with uncomplicated T2DM, they should be given the necessary training to improve their physical activity and regulate HDL level. Also, empowering them in this matter improves their QOL.